Organisasi Negara-Negara Persemakmuran Inggris: Kesuksesan Filosofi Inggris dalam Mendominasi Kolonialisme dan Imperialisme Modern - Arief Hidayat; Muhammad Fendi Aditya (SOLIDARITY: Journal of Social Studies, 2021)
This article give description about the commonwealth of nation right still active until now, although right now colonialism and imperialism the end, means this organization the unity from exs British imperium  to get strong unity  use the British Queen to symbol unity on difersity, on the fact all’nt country exs British imperium, and the next more detail descript british philosophy the name Anglo Saxon philosophy full domination that colonialism imperialism more specially after industrial revolution, the global British domination, from riset result get accuracy fact with strong coleration to get born The Commonwealth of  exs British emperor, truely the practice the anglo saxon philosophy in all subject, this philosophy to influence British police to the British territory, the character, culture and british language domination right now, public mentality, discusse that British policy about land emperor very different with the european land conintal country, especially psycologychal approach , the culture, language, and including preparing the colonies for independence, thus giving a different color in the history of world imperialism and colonialism.